Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12866-021-02213-2
|View full text |Cite
|
Sign up to set email alerts
|

The potential and effects of saline-alkali alfalfa microbiota under salt stress on the fermentation quality and microbial

Abstract: Background The objective of this study was to evaluate the chemical compositions and microbial communities of salt-tolerant alfalfa silage. Salt-tolerant alfalfa was ensiled with no additive control, and cellulase for 30 and 60 to 90 days. In this study, the dry matter (DM) content of the raw material was 29.9% DM, and the crude protein (CP) content of the alfalfa was 21.9% CP. Results After 30 days of fermentation, the DM content with the cellulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
4
3
2
Order By: Relevance
“…Bacteroidetes was positively correlated with PA, LA, and AN and negatively correlated with NDF, ADF, and WSC, probably because Bacteroidetes is mainly involved in the hydrolysis of complex macromolecules [ 52 ]. In addition, Sa et al reported that Chloroflexi is associated with acid production [ 53 ], but our results showed no correlation between Chloroflexi and organic acid (LA and AA). We could speculate that Chloroflexi only accounted for 0.01% of the bacterial community and that the effects of Chloroflexi on fermentation were negligible.…”
Section: Discussioncontrasting
confidence: 91%
“…Bacteroidetes was positively correlated with PA, LA, and AN and negatively correlated with NDF, ADF, and WSC, probably because Bacteroidetes is mainly involved in the hydrolysis of complex macromolecules [ 52 ]. In addition, Sa et al reported that Chloroflexi is associated with acid production [ 53 ], but our results showed no correlation between Chloroflexi and organic acid (LA and AA). We could speculate that Chloroflexi only accounted for 0.01% of the bacterial community and that the effects of Chloroflexi on fermentation were negligible.…”
Section: Discussioncontrasting
confidence: 91%
“…Similarly, Bai et al (2021) also discovered that the expression of the carbohydrate metabolism pathway was connected to the relative abundance of total L in the bacterial community. The abundance of amino acid metabolism, nucleotide metabolism, and cofactor and vitamin metabolism gradually increased with fermentation, which contradicted the findings of Sa et al (2021) who observed that amino acid metabolism, nucleotide metabolism, and metabolism of cofactors and vitamins were decreased in the inoculated silages during the fermentation stage. This might be because the raw materials attached to L and WSC content were low, while the exogenous additives contributed to the increase in this metabolism.…”
Section: Discussioncontrasting
confidence: 80%
“…In the present study, Pantoea was found to be the most common facultative aerobic genus in FM. Pantoea has been observed in fresh native grass ( You et al, 2021 ), alfalfa ( Sa et al, 2021 ), and soybean ( Ni et al, 2017 ). Pantoea abundance decreased after 30 days of fermentation, which might be attributable to their great sensitivity to pH decline ( Ogunade et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…LEfSe analysis was used to further analyze the differences in bacterial communities between treatment groups. Among the YL groups, Proteobacteria, Enterobacter , and Pantoea were the common microorganisms in silage feedstock, and their growth and reproduction were inhibited and abundance decreased significantly after silage fermentation, so they were the differential microorganisms with respect to silage, which is in agreement with the results of Li et al [ 64 ] and Sa et al [ 65 ]. The differential bacteria in the CK group were Enterobacteriaceae and Limosilactobacillus .…”
Section: Discussionsupporting
confidence: 90%